Adaptation Time Model Based on Difference in Genders - Muhammad Zahirulhaq Ahmad; Encik Ahmad Fu'ad Idris (Research Progress in Mechanical and Manufacturing Engineering, 2024)
Thermal comfort is the state of mind in which a person feels physically comfortable with the temperature and humidity in their environment. Adaptation time refers to the amount of time it takes for a person to become comfortable in a new thermal environment. This study aimed to investigate the effects of thermal comfort and adaptation time on the Predicted Mean Vote (PMV) responses from males and females, using the ASHRAE 55 standard and a 7-point thermal sensation scale. A total of 10 participants, 5 males and 5 females, were recruited and exposed to different thermal environments under controlled conditions. The thermal comfort of the participants was evaluated using the ASHRAE 55 standard and the 7-point thermal sensation scale. The results of the study revealed that females had a lower thermal comfort level, a longer adaptation time, and higher PMV response compared to males. Furthermore, the results showed that the ASHRAE 55 standard and 7-point thermal sensation scale were effective tools in measuring the thermal comfort of participants. These findings suggest that males and females may have different physiological responses to thermal environments. Additionally, this study can determine the relationship between the adaptation time and temperature difference for males and females, which is established through statistical analysis. As a result, the equation for the male adaptation time is  , and the correlation of R2 is 0.794 and R is 0.859. While female adaptation time  is, the correlation of R2 is 0.776 and R is 0.881. According to the equation, the temperature difference determines how long it takes for males and females to adapt to an air-conditioned room, and the higher the temperature differential, the longer it takes. In conclusion, the discovery can aid in the prediction of adaption time for better outcomes in the data collection of thermal comfort